Amelia Bedelia makes a friend - Parish, Herman; Avril, Lynne, 1951- (New York : Greenwillow Books, 2011)
Young Amelia Bedelia manages to make a friend in spite of the fact that she is often confused.
"1, Beginning reading."
1.5
K-3
K-3
Keywords: Amelia-Bedelia (Fictitious character) -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Neighbors -- Juvenile fiction; Amelia-Bedelia (Fictitious character) -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Neighbors -- Fiction; Amelia-Bedelia (Fictional character) -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Neighbors -- Fiction; Readers (Elementary).